Modulating the structure of lamb myofibrillar protein gel influenced by psyllium husk powder at different NaCl concentrations: Effect of intermolecular interactions. (15th December 2022) - Zhu, Ning; Zang, Mingwu; Wang, Shouwei; Zhang, Shunliang; Zhao, Bing; Liu, Meng; Li, Su; Wu, Qianrong; Liu, Bowen; Zhao, Yan; Qiao, Xiaoling
Highlights: PHP was proposed to alleviate textural deterioration of MP gels in low NaCl. The effects of PHP on the MP gels properties were dose-dependent. PHP could insert into hydrophobic cavity of MP, causing the unfolding of α-helix. PHP improved the viscoelasticity, thermal stability, molecular forces of MP gels. Molecular docking simulation could be used to further verify the strategy. Abstract: In this study, a strategy involving psyllium husk powder (PHP) was proposed to alleviate the textural deterioration of protein gels under low-sodium conditions. Results revealed that myofibrillar protein (MP) in 0.3 M NaCl could accommodate more PHP to achieve better gels properties compared with that of 0.6 M NaCl. The 3 % addition of PHP could lessen the textural deterioration of gels at 0.3 M NaCl because of the insertion of PHP into the hydrophobic cavity of MP. Consequently, the reduction in protein viscoelasticity and the thermal stability of the head and tail of myosin improved. α-Helix structures unfolded, intermolecular forces formed, and proteins aggregated. Molecular docking predicted hydrogen bonds and hydrophobic interactions as the main forces to stabilize the conformation of composites. Experiments further verified that hydrophobic interactions and disulfide bonds were the main forces that stabilized the structure of MP–PHP composite gels.